Os filhos de Malinche: as representações sobre os indígenas na ótica de Diego Rivera (1920-1940) - Jacob, Jorcy Foerste (2014)
In this work we are going to analyses the representations about Indians, made by Diego Rivera as muralist painter. The Mural Painter Movement made part of the politics of the post-revolutionary Estate for the construction of one modern nation as in the western world concept. The main problem was how to include in this nationalist ideal the distinct groups that made part of the revolutionary process, among them, the numerous Indians populations socially, economic and culturally excluded from the Mexican society. Joint in an anthropological perspective, was formulated the Indigenism, a systemic and unilateral politic for Indians with the ideal to made them Mexicans. This project had as main objective, to protect the true and unique Mexican identity, the mixed race between westerns and Indians culture. This context, officially arises in 1922, the Mexican Muralism. It appears as a fundamental element to spread the representations about to be Mexican, and therefore, essential for the symbolic legitimation of the National Estate. In the meantime, as well the institutional indigenist speech presented variations, since his intellectuals didn‘t say in only one perspective, the muralists didn‘t represent the Indians and the nation in unique terms. This way, we‘re going to work with handwritten and mural pictures from the years 1920 to 1940 made by Diego Rivera. The objective is to understand how the painter had appropriated of the indigenist speeches from that time and produced his representations of the Indians and the nation.